Dehydrative Allylation of Amine with Allyl Alcohol by Titanium Oxide Supported Molybdenum Oxide Catalyst - Kon, Yoshihiro; Nakashima, Takuya; Fujitani, Tadahiro; Murayama, Toru; Ueda, Wataru (Synlett, 2019)
The dehydrative allylation from allyl alcohol with amines to generate various allyl amines by MoO3/TiO2 solid catalyst is described. The catalyst can be reused at least three times without a decrease of activity.
Keywords: allyl amine; molybdenum oxide catalyst; allyl alcohol; titanium oxide; dehydrative allylation